Historic Interior Scheme (HIS) conservation framework for heritage museum building in Malaysia / Norashikin Abdul Karim ... [et al.] - Abdul Karim, Norashikin; Harun, Siti Norlizaiha; Ayob, Salwa; Hazim, Zulkarnain (2021)
The heritage museum building has seen rapid growth in the past few decades in Malaysia. It is an important national heritage asset where it needs to be preserved. This heritage asset has its own attractiveness and their historical significance not only the exterior but the interior of the museum building. It carries a different uniqueness of historic interior scheme where each of the museum building filled with different interior features, room function, spatial design, variety of historic material, and finishes and has its own historic event inside. Unfortunately, these historic interior scheme significances have disappeared due to the exhibition purpose and museum needs. For that reason, the historic interior scheme conservation framework for heritage museum building is needed. Hence, this framework's aims to give guidance in preserving the historic interior scheme of the heritage museum building. The objectives to be achieved by proposed this framework are to authenticate the level of change (LoC) on the historic interior scheme which influences the authenticity of heritage building conservation and to verify the degree of acceptance (DoC) of heritage exhibition interpretation practice according to the heritage building museum standard of the historic interior scheme. The method that has been applied in earned this framework is by evaluating 4 gazetted heritage museum buildings: Penang Malay Gallery, George Town Penang, National Education Museum, UPSI, Tanjung Malim Perak, History and Ethnography Museum, Malacca, and Kelantan Royal Custom and Tradition Museum, Kelantan. The evaluation approach is used by using the evaluation form to obtain the data. Two evaluations that involved in this research; Historic Interior Scheme (HIS) Evaluation and Heritage Exhibition Scheme (HES) Evaluation. This evaluation was carried out with the support of observation on-site, measured drawings, documents study, site tour and referred to curators and museum experts. The photographic mapping technique using the historic photograph, sketches, drawings, books, and journals was applied to investigate the origin of the museum's building interior space. The findings indicated that this conservation framework is certified important for acquiring appropriate historic interior schemes with the right historic interpretation for the convince heritage museum building's exhibition in the future.